EXPLORING FACTORS CAUSING LISTENING ANXIETY ON GENERATION Z STUDENTS - Neni Nurkhamidah (Acitya: Journal of Teaching and Education, 2020)
Listening is a complex process because listeners do not only listen to the words, but they also interpret speakers' utterances. This complexity and difficulty triggers student’s anxiety. Many researches find out that listening anxiety affect students’ performance. Therefore, study on listening anxiety is crucial to be carried out. This study is conducted to find out the factors causing listening anxiety on generation Z students that raised with technology and have more opportunity to listen English from many sources than the previous generation. This is a qualitative study that is conducted in English Department of STKIP MNC by involving 20 participants from Basic Listening class. The finding shows that there are some factors causing students listening anxiety. The factor is categorized in two sources; students and technological factors. The internal factors trigger students listening anxiety are rate of speech, vocabulary and accent, and concentration. On the other hand, technological factor causing listening anxiety comes from the poor quality of audio sounds from speaker used in the class.